Konsep Akhlak Mulia dalam Tutur Kata Menurut Tafsir Al-Azhar: Sebuah Pendekatan Etika Komunikasi dan Maqāṣidī - Kurniawan, Anang; Ikhwanudin, M.; Amin, Muhammad Nur (Journal of Islamic Scriptures in Non-Arabic Societies, 2025)
This study explores the concept of noble character (akhlāq karīmah) in verbal communication based on Tafsir al-Azhar by Buya Hamka, employing a thematic (mawḍū‘ī) approach to Qur'anic interpretation. The research addresses the increasing degradation of ethical discourse in Indonesia's public sphere, particularly in digital and political contexts. By analyzing key Qur'anic verses—such as QS. Al-Baqarah [2]:83, QS. Al-Isrā’ [17]:53, and QS. Al-Ḥujurāt [49]:12—alongside Hamka’s commentary, this paper highlights the integrative ethical framework within Islamic communication. The findings demonstrate that Buya Hamka emphasizes three core principles: honesty, kindness and politeness in speech, and linguistic accuracy in social interactions. These values are linked to the higher objectives of Islamic law (maqāṣid al-sharī‘ah), particularly hifẓ al-nafs (protection of life), hifẓ al-‘aql (protection of reason), and hifẓ al-‘irdh (protection of dignity). Furthermore, the study incorporates contemporary sociological and communicative theories to contextualize Hamka's interpretations, showing their continued relevance in fostering moral discourse in today’s society.